Effect of Different Salinities on the Biochemical Properties and Meat Quality of Adult Freshwater Drum (Aplodinotus grunniens) During Temporary Rearing - Wanwen Chen; Sharifa Mohamed Miraji; Yu Tian; Xueyan Ma; Wu Jin; Haibo Wen; Gangchun Xu; Pao Xu; Hao Cheng (MDPI AG, 2024)
Salinity is a significant environmental component that affects the physiological state of aquatic species. This study aimed to investigate whether water salinity had an impact on the biochemical properties and meat quality of adult Aplodinotus grunniens during temporary rearing of 7 days. Salinity caused increased osmotic pressure and antioxidant enzyme activities of Aplodinotus grunniens, which were attributed to the increase in the content of alanine and glutamate. It raised the hardness and shear force with an increase in salinity, leading to an increase in water-holding capacity. Salinity enhanced the DHA ratio with a decrease in the atherosclerotic index and thrombosis index. Combined with the increase in flavor amino acids and nucleotides, salinity enhanced the umami taste of Aplodinotus grunniens. These findings suggest that temporary rearing in salinity might be a practical approach to improving the meat quality of adult Aplodinotus grunniens.